2022
DOI: 10.1155/2022/1415142
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Beliefs and Practice Evaluation Based on Artificial Intelligence Models under the IP Environment

Abstract: The digitization of thought theory is not yet sufficient to meet the needs of the students. It is very necessary to strengthen the construction of ideological and political (IP) courses, strengthen the education of mainstream ideology, and occupy the initiative of discourse. There are effective ways and means to study the deep integration of information technologies into the new age of philosophy and philosophy education of students, which can greatly improve the quality of teaching and the effectiveness of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Additionally, they explore the potential of AI, IoT, and deep learning models to enhance teaching methods, emotional analysis, and sentiment analysis. These studies pave the way for innovative approaches to ideological and political education, promoting student engagement, mental well-being, and personalized learning experiences [ [38] , [39] , [40] , [41] ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they explore the potential of AI, IoT, and deep learning models to enhance teaching methods, emotional analysis, and sentiment analysis. These studies pave the way for innovative approaches to ideological and political education, promoting student engagement, mental well-being, and personalized learning experiences [ [38] , [39] , [40] , [41] ].…”
Section: Resultsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%